Keeping the submission going to new entitled of journal - Zahra Lorigooini (Shahrekord University of Medical Sciences, 2022)
Our journal is presently known as Future Natural Products, previously Advanced Herbal Medicine (2015- 2021). Journal of Future Natural Products, Trendy, is the same old journal that was retitled in 2021 by the editorial board and intended to be published in the succeeding areas more energetically than before. With the assistance of academics, we hope this new scientific field will become an appropriate field for this journal's growth in various indexes. It can also make the site more visible and view more articles in this magazine with high visibility. Future Natural Products is an international, free of charge, peer-reviewed, and open-access journal devoted to publishing original research articles, review articles, meta-analyses, editorials, letters to editors, and brief communications in the field of "Future Natural Products" involving both basic and clinical research. The journal has a distinguished editorial board with extensive academic qualifications, ensuring that it maintains high scientific standards and has broad international coverage.